Fahr's Disease: A Case Report - Sinha, Rahul; Sodhi, Kirandeep; John, BM; Singh, Daljit (Journal of Nepal Paediatric Society, 2009)
We report a case of Fahrs disease in a 15year old girl presented to us with focal seizure with secondary generalisation. Clinically there were no abnormal findings. The CT scan (brain) showed multiple symmetric and extensive calcifications in the basal ganglia, thalamus, and dentate nucleus, subcortical white matter of cerebral and cerebellar areas. Presently the child is under followup with good seizure control with carbamezpine. This rare case of idiopathic Fahr's disease in a child, which has never been reported in Indian literature has been brought out to highlight this unusual condition and its differentiation from the commoner Fahr's syndrome. Key words: Basal ganglia, calcification, Fahrs disease. DOI: 10.3126/jnps.v30i1.2459 Journal of Nepal Paediatric Society Vol.30(1) 2010 44-45